Analyses of Daily Market Impact Using Execution and Order Book Information - Yamada, Kenta; Mizuno, Takayuki (Frontiers in Physics, 2020)
We analyzed the Tokyo Stock Exchange (TSE) for a 29-month period from August 2014 to December 2016, including every transaction and order book snapshot, and confirmed that the market impact depends on each stock by a simple statistical test. We found that the market impact slowly changes over time based on a correlation analysis of it. From order book analysis, the negative correlation were found between the market impact and averaged limit order volumes on order book. We also clarified that one of the factors of market impact is the volume of limit orders on order book.